The Development and Effect Evaluation of the Newlyweds’ Relationship Education Program in China - Xu, Honghong (Advances in Social Sciences Research Journal, 2022)
This study aimed to examine the application and effect of intimate relationship education program. 9 newlywed Chinese couples participated in this educational workshop program. The workshop was designed to help couples enhance mutual understanding, explore gender differences, learn about conflicts and coping strategies, promote emotional management skills. The study also used interviews to explore the effect mechanism of the educational workshop, and this kind of educational program was proved to be applicable and effective in helping newlywed couples to improve communication and self-management skills, and it might be helpful to decrease the future risk of marital dissolution.